PERIOPERATIVE ANAPHYLAXIS CAUSED BY MUSCLE RELAXANTS: DO WE KNOW ENOUGH? - Marković, Danica; Vuković, Natalija; Milenković, Jelena; Marković-Živković, Bojana; Budić, Ivana (Srpski medicinski časopis Lekarske komore, 2022)
Perioperative anaphylaxis caused by muscle relaxants represents a relatively rare, albeit a serious complication during anesthesia. It can result in serious morbidity or even mortality. This reaction usually happens before or after intubation of a patient, that is, a few minutes after muscle relaxant administration. The beginning of the reaction can be missed, even by the most experienced anesthesiologist, since its recognition depends on the severity of the symptoms. There are no guidelines specific to the therapy of muscle relaxant anaphylaxis and therefore therapy is based simply on the general guidelines. Also, in many countries, there are no registries of the incidence of anaphylaxis caused by muscle relaxants. Therefore, this is an extremely important subject for anesthesiology practice, and it requires more attention.